Implementation of AI-Based Chatbots to Enhance Efficiency and Transparency in Land Certification in Indonesia - Oktavia, Chaulina Alfianti; Pribadi, Risky Feryansyah (Tunas Agraria, 2025)
This study explored the implementation of artificial intelligence (AI)-based chatbots to improve the land certification process in Indonesia. The primary objective was to evaluate how chatbots could address key challenges such as accessibility, transparency, and efficiency in obtaining land certification information. A chatbot system was developed and tested to provide users with basic information about the land certification process, including document requirements, registration procedures, and verification methods. The methodology involved collecting user feedback through a survey and evaluating the chatbot’s performance in terms of response accuracy and user satisfaction. The results indicated that the chatbot successfully answered 85% of general queries accurately, with 80% of users expressing high satisfaction with the system. However, challenges were encountered in addressing more complex, legally oriented queries. The discussion suggested that while the chatbot was effective for routine questions, further improvements in the knowledge base, integration with government systems, and the user interface are required to enhance its functionality. The study concludes that AI-powered chatbots have the potential to streamline the land certification process, but future developments are necessary to fully address the complexities of legal and procedural inquiries. The integration of expert systems and real-time updates could further improve the chatbot’s efficiency and user engagement.   Penelitian ini mengeksplorasi implementasi chatbot berbasis kecerdasan buatan (AI) dalam meningkatkan efisiensi dan transparansi proses sertifikasi tanah di Indonesia. Tujuan utamanya adalah menganalisis bagaimana sistem ini dapat mengatasi tantangan utama dalam aksesibilitas informasi, transparansi prosedur, dan efisiensi layanan sertifikasi tanah. Sistem ini yang dikembangkan dirancang untuk memberikan informasi dasar mengenai sertifikasi tanah, termasuk persyaratan dokumen, prosedur pendaftaran, dan metode verifikasi. Metode penelitian melibatkan pengumpulan umpan balik pengguna melalui survei serta evaluasi kinerja chatbot berdasarkan akurasi respons dan tingkat kepuasan pengguna. Hasil penelitian menunjukkan bahwa chatbot mampu menjawab 85% pertanyaan umum dengan akurasi tinggi, sementara 80% pengguna menyatakan kepuasan terhadap sistem ini. Namun, ditemukan tantangan dalam menangani pertanyaan yang lebih kompleks dan berkaitan dengan aspek hukum. Hasil diskusi menunjukkan bahwa meskipun chatbot efektif dalam menjawab pertanyaan rutin, peningkatan lebih lanjut diperlukan dalam pengembangan basis pengetahuan, integrasi dengan sistem pemerintah, serta optimalisasi antarmuka pengguna guna meningkatkan fungsionalitasnya. Studi ini menyimpulkan bahwa chatbot berbasis AI memiliki potensi untuk menyederhanakan proses sertifikasi tanah, tetapi pengembangan lebih lanjut diperlukan untuk mengatasi kompleksitas hukum dan prosedural. Integrasi dengan sistem pakar dan pembaruan informasi secara real-time dapat lebih meningkatkan efisiensi dan keterlibatan pengguna.